Stress management for dummies - Elkin, Allen (--For dummies., 2013)
Tired of letting stress have a negative impact on your life? Easy. It's impossible to get through life without encountering stress. And unfortunately, most of us learn the incorrect ways to cope with it. Thankfully, Stress management for dummies gives you trusted, time-tested guidance on teaching your body and mind to properly cope with stress while keeping your sanity intact. Whether it's love, work, family, or something else that has you in the red zone, this updated edition of Stress Management For Dummies will help you identify the stress triggers in your life.